Perceived community impact study: findings from KTP 10th Malaysia Plan - Surif, Misni; Madon, Zainal; Abu Samah, Asnarulkhadi; Sulaiman, Abdul Hadi (Knowledge Transfer Programme, 2017)
Knowledge Transfer Program was developed to stimulate the involvement of the Government-University-Organization (community and local industry) through sharing and exchange knowledge from university to the organizations. A question arise on how far the effectiveness of this KTP achieves the set objectives. Thus, a study was conducted to evaluate the impact and effectiveness of KTP in the targeted communities involved in Rolling 1 and Rolling 2. Six indicators were developed to measure community impact effectiveness including application, sustainability, influence others, mentoring, benefit and well-being. A total of 200 participants from different KTP community projects were involved in this survey. The study revealed that knowledge transfer program in Malaysia has positively impact the individuals and community particularly among KTP’s community group. Participants realized the benefit of knowledge they gained, improved in their well-being.